Enzymatic degumming of silk with microbial proteases - More, Shivaji V.; Khandelwal, Harish B.; Joseph, M. A.; Laxman, Ryali Seeta (Journal of Natural Fibers, 2013)
Degumming of Chinese bivoltine silk with alkaline proteases from various microbial sources was investigated and compared with commercial enzymes. Among the proteases tested, two fungal and two actinomycete proteases were promising, which showed weight loss similar to conventional method (19.58% to 21.78%). Conidiobolus brefeldianus and BOA-2 proteases were best enzymes, which showed weight loss similar to conventional method with low enzyme concentrations and in shorter time. No significant differences were found in tensile strength or elongation at break by enzymatic degumming indicating that there was no damage to the fiber. Scanning electron micrographs showed the sericin deposits were removed and the fibers were separated.
Keywords: Alkaline Protease; bivoltine; degumming; microbial; Silk; weight loss

Uptake of Azo dyes into silk glands for production of colored silk cocoons using a green feeding approach - Nisal, Anuya; Trivedy, Kanika; Mohammad, Hasan; Panneri, Suyana; Sen Gupta, Sayam; Lele, Ashish K.; Manchala, Ramesh; Kumar, Nirmal S.; Gadgil, Mugdha; Khandelwal, Harish B.; More, Snehal; Laxman, Ryali Seeta (ACS Sustainable Chemistry & Engineering, 2014)
Dyeing of textile fabrics is considered to be one of the most polluting industries today, and there is a need to develop green processes that can reduce this pollution. A promising technology that can potentially cleanup the dyeing of silk fibers that are widely used for textile applications would involve the generation of intrinsically colored silk cocoons. This can be achieved by feeding of Bombyx mori silkworm larvae with a modified feed of mulberry leaves containing a sprayed dye solution. This process significantly reduces the need for treating toxic dye effluents that are generated in traditional dyeing processes. In this report, we have evaluated a set of seven different azo dyes that are used in the textile industry for dyeing to produce intrinsically dyed silk. The dyes used in the study had similar chemical structures with systematically varying partition coefficients. The results suggest that while some dyes produced intrinsically colored silk other did not. Careful evaluation of the physical properties of these related azo dyes suggest that the balance of hydrophobic and hydrophilic character is necessary for diffusion of the dye from the alimentary canal of the silkworm larva into the hemolymph and later into the silk glands. The partition coefficient of the dye also determines the preferential association of the dye with either sericin or fibroin protein in the silkworm gland and finally into the cocoon. These insights are extremely important in development of novel dye molecules that can be successfully fed to Bombyx mori silkworm larvae for producing intrinsically colored silk of various colors and shades.
Keywords: Azo dyes; Biochemical pathways; Color silk; Dye uptake; `' Green `' silk

Eco-friendly enzymatic dehairing of skins and hides by C-brefeldianus protease - Khandelwal, Harish B.; More, Snehal V.; Kalal, K. M.; Laxman, Ryali Seeta (Clean Technologies and Environmental Policy, 2015)
Alkaline protease from Conidiobolus brefeldianus was efficient in unhairing various types of skins and hides. The crude protease preparation was active toward keratin-azure, elastin-orcin, azocasein, and azocoll, but did not show true collagenase activity. In addition, the crude enzyme exhibited other enzyme activities such as chondroitinase, laminarase, and chitinase. Complete hair removal of skin/hide by the protease achieved in 16-18 h. The dehaired pelt showed smooth and white appearance due to hair removal along with epidermal layer. In addition, the grain was clean and without damage in enzymatically dehaired pelts. The microscopic observation of the cross-section of dehaired goat skin and cow hide showed absence of epidermis, hair shaft with empty follicles. Enzymatic dehairing resulted in complete and uniform fiber opening in the dermis and corium region. Physical properties viz. tensile strength, elongation, and tear strength of dyed crust of enzymatically and conventionally dehaired pelts were comparable. Results were also validated on large scale with goat skins and cow hides.
Keywords: Alkaline Protease; Conidiobolus brefeldianus; Cow hides; Dehaired pelts; Enzymatic dehairing; Sheep skins